FUNDAMENTALS OF CONVENTIONALITY CONTROL: THE INTERNATIONAL LAW OF HUMAN RIGHTS OMNIPRESENT - Bolaños Salazar, Elard Ricardo (2019)
This article develops the foundations of the socalled conventionality control, understanding this legal institution as the obligation that all the authorities of a State have to contrast the internal law with the International Law of Human Rights. Thus, it is concluded that the best for a real understanding of this technique, is to put, above all things, respect and the guarantee of the rights and freedoms of people.